Customary Law in the New Indonesian Criminal Code: Recognition or Reduction? - Susanto, Yoghi Arief; Prabawani, Riski Dysas; Aulia Najah, Naily (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
The new Indonesian Criminal Code, as stipulated in Article 2 of Law No. 1/2023, formally acknowledges customary criminal law as the basis for determining criminal liability. Its implementation is further specified in government regulations, as guidelines for regions in formulating laws that reflect community-based principles. However, this arrangement potentially engenders legal issues, including jurisdictional conflicts and the erosion of local wisdom. This study seeks to analyse whether the provisions represent a recognition or reduction of customary criminal law. The analysis is grounded in the legal pluralism theory, which emphasises the interaction between various legal systems in society, and the theory of law and society, which views law as a social phenomenon shaped by local values and culture. As doctrinal research, this study utilises primary and secondary legal materials, employing a qualitative analysis approach informed by legal hermeneutics. The findings suggest that Article 2 of Law No. 1/2023, concerning the Criminal Code, acknowledges the validity of customary criminal law in Indonesia. From theoretical, legal, and practical perspectives, this provision plays a crucial role in Indonesian judicial practice. However, such recognition should not be construed as subordination within a hierarchical regulatory framework that could undermine the autonomy of customary criminal law. Instead, it should serve as a framework for legal coexistence, where mutual respect is fostered as an adaptation to the challenges of global complexity, thus preserving Indonesia’s pluralistic legal identity.